The interest in online museum experiences and the influence of uncertainty and sentiment factors on tourist arrivals: The case of EU Mediterranean countries - Bernardina Algieri; Arturo Leccadito; Rosetta Lombardo (Annals of Tourism Research Empirical Insights, 2023)
This study examines the determinants of tourist arrivals at hotels and short-stay accommodations for nine EU countries from January 2010 to March 2022. We identify four driving channels of foreign and domestic tourism flows: a traditional, a sentiment, a technological and a health channel. The latter comprises two novel variables: the museum search interest and the infectious disease equity market volatility tracker. The results reveal that traditional and new drivers related to market sentiments and interest in online tourism experiences affect arrivals. Notably, there is a substitution effect between online and in-presence tourism, and the larger the uncertainty, the more substantial the reduction in tourist arrivals. COVID-19 has affected especially Spain and Italy and more foreign than domestic tourists.
Keywords: P48; Q55; Z32; 330; Competitiveness; Google trends; Infectious disease equity market volatility; Online museums; Poisson and negative binomial panel models; Sentiment; Tourism demand